MONITORING LAND COVER CHANGE INDICATIVE MAP OF SOCIAL FORESTRY AREA IN PULANG PISAU REGENCY - Putri, Ananda; Marcoleos, Shandy; Pratama, Yogian; Meklie; Iskandar, Beni (Jurnal Belantara, 2025)
Pulang Pisau Regency faces significant pressure from human activities that threaten the sustainability of its forests. The phenomenon of deforestation and land conversion is important for understanding the dynamics of land cover change. Social forestry programs potentially contribute to reducing the rate of change in forest cover. This study aims to analyze land cover change on the Indicative Social Forestry Map (PIAPS) in Pulang Pisau Regency. The research method used Landsat-7 images recorded in 2000 and Landsat-8 images recorded in 2020, PIAPS data, and land cover classification using the Random Forest model with Quantum GIS and Google Earth Engine (GEE) software. The research shows that there has been a significant land cover change over a decade in the Indicative Map of Social Forestry in Pulang Pisau District. Forest cover has decreased from 41,149 ha in 2000 to 23,836 ha in 2020. The average accuracy of land cover showed an OA value of 95% and KA of 92%, which is categorized as good. This study thus highlights the importance of maintaining forest cover to address future land change dynamics through social forestry scheme programs